Design of a pressure controller for a thermal evaporation system / Ahmad Suffian Muhammad - Muhammad, Ahmad Suffian (2009)
This project describes the method of designing a pressure controller for vacuum pressure control system well suit for evaporation and deposition of amorphous silicon thin film. The constant total pressure or pressure not less than I 0·5 torr is required during the conditioning of the vacuum to control impurity in high temperature. The pressure controller was designed to maintain the constant total gas pressure inside vacuum chamber. This controller consists of pressure sensor circuit and relay switching which. The pressure inside the chamber will detect by using the vacuum sensor which also known as pressure sensor. The pressure sensor also as the transducer gives the signal to the pressure sensor circuit. The pressure sensor circuit will provide the signal that used by relay switching circuit to switch off the pump operation. The circuit was designed and simulated by using OrCAD PSpice software. After analysis and simulation, the circuit was successful designed to amplify the low level voltage to the high level voltage. The combination of pressure sensor circuit and a relay switching will yields a pressure controller, which is to control the pressure inside the vacuum chamber.